INCREMENTAL LABOUR OUTPUT RATIO (ILOR) AND OUTPUT GROWTH IN INDONESIA IN THE SHORT TERM - Desfitrina; Zulfadhli (PT. Jurnal Center Indonesia Publisher, 2026)
This study specifically projects output and predicts economic growth, investment needs, and additional labor requirements sectorally, using labor and output data (GDP by business field at constant prices) for the period 2001-2019. The analysis method used is labor projection based on the output approach, namely the Incremental Labor Output Ratio (ILOR). The results of the study show that (1) the increase in output in the agricultural sector does not have an impact on the expansion of labor absorption in the sector, but the conditions contrast with the increase in output in the public services, mining and trade sectors which will have an impact on the expansion of labor (2) Additional labor in the agricultural sector does not provide optimal results or additional labor in the agricultural sector and has an impact on decreasing output in the future (3) Additional labor in the mining sector will result in high output in the future.